2006
DOI: 10.1007/s00586-005-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hominis deep wound infection after neuromuscular scoliosis surgery: the use of real-time polymerase chain reaction (PCR)

Abstract: Mycoplasma hominis is a commensal of the genitourinary tract. It mostly causes infections to associated structures of this system; however, occasionally it is a pathogen in nongenitourinary tract infections. Since, M. hominis strains require special growth conditions and cannot be Gram stained, they may be missed or delay diagnosis. This report describes a deep wound infection caused by M. hominis after neuromuscular scoliosis surgery; M. hominis was recovered by real-time polymerase chain reaction (PCR). An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It is usually responsible for genitourinary tract infections and gynecological surgical wounds infections [13,14]. A review of extragenital infections involving M. hominis revealed that they fall into five categories: septicemia, joint infections, central nervous system infections, respiratory tract infections, and wound infections (particularly after surgery) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually responsible for genitourinary tract infections and gynecological surgical wounds infections [13,14]. A review of extragenital infections involving M. hominis revealed that they fall into five categories: septicemia, joint infections, central nervous system infections, respiratory tract infections, and wound infections (particularly after surgery) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients were found to be debilitated or immunocompromised before the infection developed [16]. Three cases of M. hominis infection were reported in literature after scoliosis surgery [13,15]. Two cases of retroperitoneal abscess due to M. hominis have been reported, one in a polytraumatized man, and the other one postpartum [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The organism lacks a cell wall and instead has a 3-layer sterol membrane, so it does not appear on Gram stain. 13 To culture M. hominis, specialized media containing animal serum are needed. 14 Polymerase chain reaction (PCR) may be the most sensitive method for diagnosis, but it is not routinely performed.…”
mentioning
confidence: 99%
“…14 Polymerase chain reaction (PCR) may be the most sensitive method for diagnosis, but it is not routinely performed. 13 For these reasons, diagnosis is often delayed. Because it is an atypical bacterium, M. hominis does not respond to common empirical antibiotics, which act on cell wall metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation